2012
DOI: 10.1073/pnas.1200017109
|View full text |Cite
|
Sign up to set email alerts
|

Elemental nitrogen partitioning in dense interstellar clouds

Abstract: Many chemical models of dense interstellar clouds predict that the majority of gas-phase elemental nitrogen should be present as N 2 , with an abundance approximately five orders of magnitude less than that of hydrogen. As a homonuclear diatomic molecule, N 2 is difficult to detect spectroscopically through infrared or millimeterwavelength transitions. Therefore, its abundance is often inferred indirectly through its reaction product N 2 H þ . Two main formation mechanisms, each involving two radical-radical r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 39 publications
10
101
1
2
Order By: Relevance
“…Our new measurements of the low temperature rates of the C + NH 3 reaction, in addition to an updated chemistry for NH, NH 2 and NH 3 coupled with recent studies of N 2 production pathways (Daranlot et al 2012;Daranlot et al 2013;Daranlot et al 2011;Loison et al 2014a;Ma et al 2012) lead to a strong disagreement between the observed and simulated abundances for NH, NH 2 and NH 3 from pure gas-phase models. In contrast, the gas-grain simulations produce good agreement with observations, a result which is essentially independent of the ortho-to-para ratio of H 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our new measurements of the low temperature rates of the C + NH 3 reaction, in addition to an updated chemistry for NH, NH 2 and NH 3 coupled with recent studies of N 2 production pathways (Daranlot et al 2012;Daranlot et al 2013;Daranlot et al 2011;Loison et al 2014a;Ma et al 2012) lead to a strong disagreement between the observed and simulated abundances for NH, NH 2 and NH 3 from pure gas-phase models. In contrast, the gas-grain simulations produce good agreement with observations, a result which is essentially independent of the ortho-to-para ratio of H 2 .…”
Section: Resultsmentioning
confidence: 99%
“…N 2 itself is produced by atomic nitrogen reactions with small neutral radicals (Daranlot et al 2012;Le Gal et al 2014) which experimental and theoretical studies have shown to be less efficient than previously assumed (Daranlot et al 2012;Daranlot et al 2013;Daranlot et al 2011;Jorfi & Honvault 2009;Loison et al 2014a;Ma et al 2012 (Vigren et al 2012) which is nonetheless sufficient to make this process the major source of NH radicals in current gas-phase astrochemical models (Le Gal et al 2014). Reaction (R1) is problematic due to the endothermicity of the N + + para-H 2 (p-H 2 ) reaction (Zymak et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that the adopted N 2 photodissociation rate is incorrect. Even in dense cores, not all nitrogen appears to have been transformed to molecular form (Maret et al 2006;Daranlot et al 2012). Observations of HCN in the surface layers of protoplanetary disks suggest that the nitrogen chemistry is strongly affected by whether or not a star has sufficiently hard UV radiation to photodissociate N 2 (Pascucci et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any CN 2 H 2 + species lying below the reagent energy level, and we consider that this reaction cannot take place. Considering only the triplet surface, the only barrierless reaction is attack on the carbon atom that leads to the ground state 3 NCN intermediate (Daranlot et al 2012;Ma et al 2012). The main exit channel is C + N 2 after isomerization of the NCN intermediate through a tight TS, and then back dissociation may be important and isotope exchange possible.…”
Section: Appendix A: Exchange Reactionsmentioning
confidence: 99%